Long term outcome of infective endocarditis in patients who were not drug addicts: a 10 year study. Issue 5 (1st May 2000) - Castillo, J C; Anguita, M P; Ramírez, A; Siles, J R; Torres, F; Mesa, D; Franco, M; Muñoz, I; Concha, M; Vallés, F
Abstract : OBJECTIVE: To determine the clinical features and long term prognosis of infective endocarditis in patients who were not drug addicts. DESIGN: Prospective case series. SETTING: A university hospital that is both a referral and a primary care centre. PATIENTS: 138 consecutive cases of infective endocarditis diagnosed and treated from January 1987 to March 1997. RESULTS: Mean patient age was 44 (20) years old. 95 patients (69%) had native valve endocarditis and 43 (31%) had prosthetic valve endocarditis. Staphylococci were the causal microorganisms in 34% of cases and streptococci in 33%. Severe complications occurred in 83% of patients and 51% of patients underwent surgery during the active phase (22% was emergency surgery). Inpatient mortality was 21%. During a follow up of 56 (44) months, 10 patients (9%) needed late cardiac surgery and seven (5% of the whole series) died. Overall 10 year survival was 71%. There were no significant differences in survival depending on the type of treatment received during the hospital stay (medical or combined medical–surgical). CONCLUSIONS: A high early surgery rate is related to good long term results and does not increase in-hospital mortality. Medical treatment, however, also offers favourable long term results in cases of responsive infective endocarditis where poor prognostic factors are absent.